GQD purification study obtained by bottom-up route aiming at the production of photocatalysts - Sakaguti, Luiz Gustavo; Fogaça, Leonardo Zavilenski; de Freitas, Camila Fabiano; Caetano, Wilker; Batistela, Vagner Roberto; Scaliante, Mara Heloisa Neves Olsen (Seven Editora, 2023)
Recent studies have shown that heterostructures composed of metal semiconductors (SC) and graphene quantum dots (QDs) have a photocatalytic performance considerably higher than that of intrinsic metallic semiconductors, this is because the GQDs reduce the electronic recombination on the surface of the CS, being still associated with the displacement of the absorption band to larger wavelengths. In the present work, graphene quantum dots were synthesized through commercial lignin (LcGQD), using nitric acid for depolymerization followed by a hydrothermal process. Analyses of the material demonstrated an average particulate size of 10.9 nm, UV-Vis absorption similar to that of other structures described in the literature, but without the presence of nitrogen peaks in the carbon structure, besides a remarkable specificity in fluorescence.  The LcGQD then has great potential for use in photocatalysis, sensors, and optoelectronics. DOI: https://doi.org/10.56238/methofocusinterv1-070